Chemical and biological characterization of emissions from coal- and oil-fired power plants. - Ahlberg, M (1983)
Emission samples were obtained from two medium-sized power plants, one fired with oil and the other with pulverized coal. Particles obtained by a miniscale plume stack gas sampler (MIPSGAS), simulating the dilution process in the plume, were subjected to detailed physical, chemical and biological characterization. Studies by scanning electron microscopy and by Coulter counter demonstrated that the particles from the oil-fired boiler were considerably larger than the particles from the coal-fired boiler. Chemical analyses revealed more organic substances and more S, Ni, V, in the oil than in the coal particles. The latter contained a larger proportion of Al, Si, Cl, K, Ca, Ti, Mn, Fe, Se, Rb, Y, Zr, Ba and Pb. Biological testing revealed a greater acute and subacute toxicity by the intratracheal route in the hamster, a greater toxicity to alveolar macrophages and a greater lung retention of BaP coated on the particles from oil combustion than on those from coal combustion. In another sampling line, employed simultaneously with the MIPSGAS-particulate sampler, the total emissions were collected, i.e., both particle and gas phase. These samples were used for chemical analyses and Ames mutagenicity test. Analyses of specific PAHs in emissions from both plants demonstrated that concentrations were below the detection limit (less than 4 ng/m3 of benzo(a)pyrene), which is in accord with an efficient combustion of the fuel. The mutagenicity of the samples were below the detection limit of the mutagenicity assay.